A 2001 Social Accounting Matrix for Kenya - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The Kenya 2001 Social Accounting Matrix (SAM) is the base for a dynamic computable general equilibrium (CGE) model of Kenya, which is an extension of the standard CGE modelling framework developed at IFPRI. The SAM disaggregates the entire Kenyan economy into 33 production sectors, of which 15 are agricultural sectors. Several structural and annual data sources such as national accounts, government accounts, balance of payments and foreign trade data, as well as the most recent IO table, SAMs for earlier base years and the 1997 Welfare Monitoring Survey for Kenya were used for the construction of the SAM.